PELABELAN VERTEX-GRACEFUL PADA GRAF-(6,8) - Gema Hista Medika; Zebbil Billian Tomi (Math Educa Journal, 2022)
There have been some previous studies on graceful vertex labeling have been carried out. This study aims to determine the vertex graceful labeling on (6,8)-graph. (6,8)-graph is a graph that has 6 vertices and 8 edges. In this study, the research is limited to (6,8)-graph which is finitely connected. This design of this research is descriptive qualitative research, in form of literature study and the data analysis technique used is non-statistical data analysis technique. From the results of the study, it was found that among the twenty (6,8)-graphs which are not isomorphic, there are 10 graphs which are vertex graceful labeling, namely J1, J3, J4, J5, J8, J15, J16, J17, J18, and J19.